Physicochemical Effects of Lactobacillus plantarum and Lactobacillus casei Cocultures on Soy–Wheat Flour Dough Fermentation - Teleky, Bernadette-Emőke (Foods, 2020)
In contemporary food production, an important role is given to the increase in the nutritional quality of foodstuff. In the bakery industry, one of the main cereals used is wheat flour (WF), which creates bread with proper sensory evaluation but is nutritionally poor. Soy-flour (SF) has increased nutrient content, and its consumption is recommended due to several health benefits. Dough fermentation with lactic acid bacteria (LAB) increases bread shelf life, improves flavor, and its nutritional quality, mostly due to its high organic acid production capability. In the present study, the addition of SF to WF, through fermentation with the cocultures of Lactobacillus plantarum and Lactobacillus casei was analyzed. Three different batches were performed by using WF supplemented with SF, as follows: batch A consisting of 90% WF and 10% SF; batch B—95% WF and 5% SF; batch C—100% WF. The fermentation with these two LABs presented several positive effects, which, together with increased SF content, improved the dough’s rheological and physicochemical characteristics. The dynamic rheological analysis exhibited a more stable elastic-like behavior in doughs supplemented with SF (G′ 4936.2 ± 12.7, and G″ 2338.4 ± 9.1). Organic acid production changes were the most significant, especially for the lactic, citric, and tartaric content.